Pengaruh Pembelajaran Cooperative dan Platform You Tube Terhadap Hasil Belajar Kewirausahaan Pada SMA Alikhlas Kota Bekasi - Widya Nuriyanti; Husain Nurisman; Toto Widiarto; Sutina Sutina; Ary Fiyanto; Arief Muda Kusuma; Sigit Widiyarto; Lidya Natalia Sartono; Indra Setiawan Purba; Melati Indah Sari Umarella (Jurnal Ilmiah Wahana Pendidikan, 2023)
Entrepreneurial learning requires the right media so that the expected results increase. This study aims to determine the effect of cooperative learning on entrepreneurial learning outcomes, and to determine the effect of the YouTube platform on entrepreneurial learning outcomes and to determine the effect of cooperative learning and the YouTube platform together on entrepreneurial learning outcomes. The method used is a quantitative method, using normality and homogeneity tests. Respondents were 30 students in class X SMA Alkhlas Bekasi High School, West Java. Retrieval of data by using interviews and filling out questionnaires on students. The results of the research data are processed normally and homogeneously. Cooperative learning variables and the you tube platform have an effect on entrepreneurship learning outcomes by 52.8%. Entrepreneurial learning requires practice and sharpness of expertise for students before graduating.